Dialectic Aspects of the Dynamics of the Economic System - Mirkovich, Kamen (Research Papers, 2012)
Economic systems undergo constant changes and development. This attributes to them the character of dynamic economic systems to whose dialectic analysis this study is devoted. Its aim is to clarify some regularities, features and specific aspects which represent or stem from their dialectic nature. Dialectics lies in the basis of the economic dynamics which, in turn, creates the dynamic economic system. The focus is on the categories of interaction, contradiction, quality and quantity, measure and size, homeostasis, essence and phenomenon, content and form, general, specific and individual, as well as other items in this order, which, in the context of the systemic approach, are realized as systemic economic categories. The overall presentation is dedicated to the dialectic nature of the emergence and realization of the economic dynamics of the dynamic economic systems.